Intestinal stem cell regulation by the hexosamine biosynthesis pathway in D. melanogaster - Mojzer, Janka (My University, 2021)
The intestinal stem cells (ISC) of the D. melanogaster midgut, which is the functional analogue to mammalian small intestine, are highly responsive to changes in nutrition. ISC employ the hexosamine biosynthesis pathway (HBP) to monitor nutritional status. HBP activity is an essential facilitator for insulin signaling-induced ISC proliferation. The midgut’s compartmentalized structure allows the study of many regulatory pathways. The regions of the midgut are characterized by distinct gene expression patterns, different histology, and physiological functions. The homeostatic regulation of intestine in fluctuating dietary conditions is poorly understood. In this study the interaction of the HBP and nutrition in the ISC population of the midgut were studied via confocal microscopy and the Longitudinal Analysis of the Midgut (LAM). The HBP was activated in different dietary conditions in ISC by feeding the flies with Glucosamine or by expressing the rate limiting enzyme Gfat2 in the ISC and their progeny. The increased clonal cell numbers suggest higher cellular turnover leading to higher stem cell proliferation rate in comparison fed versus starved dietary conditions. LAM gives a region-specific elevation of the clonal numbers of the cell. When experimenting which nutrients mediate the proliferative capacity of stem cells, we found that removing essential amino acids have similar effect on R4 region compared to the starved versus fed condition. Our results give new insights to the nutritional response and the region-specific activation for further research in connection with the HBP activation.